Out-of-pocket costs for paediatric admissions in district hospitals in Kenya - Barasa, E; Ayieko, P; Cleary, S; English, M (2012)
Objective To describe out-of-pocket costs of inpatient care for children under 5years of age in district hospitals in Kenya. Methods A total of 256 caretakers of admitted children were interviewed in 2-week surveys conducted in eight hospitals in four provinces in Kenya. Caretakers were asked to report care seeking behaviour and expenditure related to accessing inpatient care. Family socio-economic status was assessed through reported expenditure in the previous month. Results Seventy eight percent of caretakers were required to pay user charges to access inpatient care for children. User charges (mean, US$ 8.1; 95% CI, 6.4-9.7) were 59% of total out-of-pocket costs, while transport costs (mean, US$ 4.9; 95% CI, 3.9-6.0) and medicine costs (mean, US$ 0.7; 95% CI, 0.5-1.0) were 36% and 5%, respectively. The mean total out-of-pocket cost per paediatric admission was US$ 14.1 (95% CI, 11.9-16.2). Out-of-pocket expenditures on health were catastrophic for 25.4% (95% CI, 18.4-33.3) of caretakers interviewed. Out-of-pocket expenditures were regressive, with a greater burden being experienced by households with lower socio-economic status. Conclusion Despite a policy of user fee exemption for children under 5years of age in Kenya, our findings show that high unofficial user fees are still charged in district hospitals. Financing mechanisms that will offer financial risk protection to children seeking care need to be developed to remove barriers to child survival. © 2012 Blackwell Publishing Ltd.